Countermeasures for aerial drones - Markarian, Garik; Staniforth, Andrew (Artech House radar library., 2021)
"This comprehensive resource explains the development of UAVs, drone threats, counter-UAV systems, and strategies to handle UAVs, focusing on the practical aspects of counter-unmanned aerial vehicle (UAV) systems and technologies. Theory, technical and operational practice with insights from industry and policing are covered, and the full rogue drone threat landscape and counter-drone technologies and systems is explored. The book provides insight into counter-drone strategy, developing effective counter-drone strategies and measures, as well as counter-drone programs and the regulatory frameworks governing the use of drones. It includes analysis of future drone and counter-drone challenges and highlights ongoing research and innovation activities and an examination of future drone technologies. Written by authors who have extensive academic, research, innovation, technical, industry and police operational investigative expertise at international level, this book is useful for the aviation sector, law enforcement and academia"--Publisher's website.